1991
DOI: 10.1002/pts.2770040508
|View full text |Cite
|
Sign up to set email alerts
|

Modified atmosphere packaging of fresh mushrooms

Abstract: The storage life o f harvested fruits and vegetables is influenced by their continued respiration and biochemical activity. Lowering the temperature, and modifying the atmosphere surrounding the product, can extend the shelf-life of the produce.Mushrooms (Agaricus bisporus) were placed into different structural containers covered with PVC films and stored at three temperatures. The effect o f key variables, such as temperature, respiration rate, critical and optimal concentrations of 0, and COz, package-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 7 publications
2
35
0
Order By: Relevance
“…These atmospheres may be considered as appropriate, since a CO 2 level of up to 5% is considered phytotoxic for mushrooms (López-Briones et al 1992). Moreover, O 2 levels below 2% might be related to anaerobic respiration in mushrooms (Beit-Halachmy and Mannheim 1992). However, at 9ºC, CO 2 and O 2 levels of 4.5% and 0.15%, respectively, were reached.…”
Section: Modified Atmospheresmentioning
confidence: 99%
See 2 more Smart Citations
“…These atmospheres may be considered as appropriate, since a CO 2 level of up to 5% is considered phytotoxic for mushrooms (López-Briones et al 1992). Moreover, O 2 levels below 2% might be related to anaerobic respiration in mushrooms (Beit-Halachmy and Mannheim 1992). However, at 9ºC, CO 2 and O 2 levels of 4.5% and 0.15%, respectively, were reached.…”
Section: Modified Atmospheresmentioning
confidence: 99%
“…However, atmospheres above 5% CO 2 are considered as phytotoxic (López-Briones et al 1992). On other hand, O 2 levels below 2% are related to anaerobic respiration in mushrooms (Burton et al 1987, Beit-Halachmy andMannheim 1992) with the consequent accumulation of ethanol and acetaldehyde and the production of offodours (Tano et al 1999), besides the risk of growth of anaerobic pathogens (Sugiyama and Yang 1975). Mushroom development is inhibited by CO 2 concentrations upper than 5% (Murr andMorris 1975, López-Briones et al 1992) and O 2 levels lower than 5% (Roy et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that spoilage might be caused by the action of bacteria on the mushroom tissue and browning of mushrooms was due to a combination of autoenzymatic and microbial action on the tissue. Storage of mushroom in prepacks and the effects of carbon dioxide and oxygen on qualities of mushrooms had been reviewed by Halachmy and Mannheim (1992). The main oxidative reactions are enzymatic browning.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study oxygen contents in trays were found to decrease sharply from 20% to 0.8% ~ 8.2% within 1 day storage. In another review by Halachmy and Mannheim (1992) recorded that modified atmosphere packaging (MAP) was not found to be necessary for mushrooms and could have a damaging effect causing anaerobic respiration as well as potential growth of anaerobic pathogens. Packaging mushrooms was essential for reducing transpiration and maintaining quality and therefore the correct water vapour transmission rate (WVTR) of the film is of great importance.…”
mentioning
confidence: 99%